2008
DOI: 10.1007/s10545-008-0965-z
|View full text |Cite
|
Sign up to set email alerts
|

Progress in expanded newborn screening for metabolic conditions by LC‐MS/MS in Tuscany: Update on methods to reduce false tests

Abstract: We report on our 6-year experience of expanded newborn screening by tandem mass spectrometry in Tuscany (Italy), the first Italian Region to screen all newborns for more than 40 inborn errors of metabolism: organization, diseases observed and updates on methods to reduce false-positive and false-negative tests are described. Blood collection is recommended between 48 and 72 h of life. Blood spots are sent daily by courier to laboratory. When a positive result occurs, two subsequent procedures are followed: for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 23 publications
1
52
0
2
Order By: Relevance
“…Sample preparation for routine screening tests is exactly as reported by la Marca et al, 13 with the exception of the butylation procedure, which is not carried out.…”
Section: Tms and Methods Validationmentioning
confidence: 99%
“…Sample preparation for routine screening tests is exactly as reported by la Marca et al, 13 with the exception of the butylation procedure, which is not carried out.…”
Section: Tms and Methods Validationmentioning
confidence: 99%
“…Mass spectrometry is extensively used in newborn screening programs for analysis of metabolites from dried blood spots (DBS) collected a few days after birth, but among the detected metabolites those due to ADA deficiency have not been included so far [19,20].…”
Section: Abbreviationsmentioning
confidence: 99%
“…In the first 6 months of the pilot project, DBS were processed in parallel by both the methods reported by la Marca et al [20] and the new screening method reported by Azzari et al [21] which is performed without butylation procedure and with the addiction of Ado and dAdo IS, both at 1 mol/L for each well.…”
Section: Newborn Screening Pilot Project For Ada-scidmentioning
confidence: 99%
“…Furthermore, the possible in-source fragmentation in the case that the target analyte is a derivative of another intact biomarker molecule and natural isotope contribution might add another challenge to MS/MS (infusion or fl ow injection) only assays (Garg and Dasouki, 2006;Piraud et al, 2003). Consequently, LC-MS/MS has been increasingly explored in the confi rmatory analysis (second-tier test) of those 'diffi cult' biomarker molecules, resulting in a reduced false-positive rate (Janzen et al, 2007;Lacey et al, 2004;la Marca et al, 2007 and2008a;Matern et al, 2007;Minutti et al, 2004).…”
Section: Introductionmentioning
confidence: 99%